Ultimate strength of single layer steel fabric reinforced concrete short wall panel / Nur Najwa Amirah Shariefuddin (Faculty of Civil Engineering, 2008)
Currently, the construction in Malaysia is using the common size for wall. The common size of wall is 102.5 x 3000 x 3200 (width: length: height). However, in the use of small size for wall panel which is called short wall panel has not been utilized. By using the short wall panel, time and cost can be reduced which in the end contributed to intelligent use of time and cost towards the economic recession. This research is conducted to determine the structural behaviour of the reinforced concrete wall panel using short wall panel. The wall panel is subjected to direct axial load through experimental work. Two wall panels reinforced with single layer steel fabric of type B375 (B7) with a dimension 75 x 500 x 1000 (Width: Height: Length) were prepared. The aspect ratio (H/L) and slenderness ratio (h/t) of the wall panel are 0.5 and 7 respectively. Grade 30 normal Ordinary Portland Cement (OPC) with water cement ratio of 0.55 was used. The wall tested under compressive axial load (without eccentricity). The end conditions of the wall panel for this study are fixed-pinned. Experimental results show that both wall panel failed in compression. The average ultimate load of both samples is 280.62 kN. The average maximum lateral displacement 5.06 mm, occurred at 375 mm height. The structural behaviour of single layer steel fabric reinforced concrete short wall panel is similar to double layer steel fabric reinforced concrete short wall panel. This research is hope to provide evidence of short wall panel and can be commercialized to the_construction field. This research gives more benefits to the country and construction field by reducing cost and time.